Study of increment of emission intensity in a cold atmospheric pressure helium plasma jet using the ADAS. (1st February 2023) - Behera, Narayan; Veda Prakash, G.
Abstract: In this paper, the Atomic Data and Analysis Structure (ADAS) has been used to study the cold atmospheric pressure plasma jet. Variation of emission intensity pattern from glass nozzle to the plasma jet tip of a helium plasma jet in ambient air has been observed from the intensified charge-coupled device (ICCD) camera image. The increase of intensity pattern towards the plasma jet tip is an important and fundamental feature of the plasma jet in ambient air. The correlation of this observed pattern with electron impact processes has been studied by computing photon emissivity coefficients (PEC) using the ADAS. The role of various atomic processes involved in this study has also been discussed.